An assessment to the use of Facebook as a communication tool by Midlands State University students from 2012 to 2013 - Masuku, Caven; Moyo, Painos (Academic Journals, 2016)
This article seeks to examine the use patterns of Facebook by Midlands State University (MSU) students as a communication tool from 2012 to 2013. It focuses on MSU students in Zimbabwe focusing on how social media networks such as Facebook can be used by university students to communicate academic, social and political issues in their day to day lives. Again, this will reflect on the efficiency and cultural impact that Facebook has in the academic world, particularly in Zimbabwe. The article will respond to issues such as: assessing the behaviour, attitude of the students themselves, and impediments they encounter when using social network sites such as Facebook. It will also analyse the uses of Facebook among college students as way of gratifying their needs, which include: establishing relationships socially and communicating with friends and family members. The article will be informed by such theories as information theory, electronic colonialism theory and the uses and gratifications theory. Only few students with access to it and with solid technological background to utilise it for social, academic and political issues maximise its availability. Facebook combines sound, still and moving images that can be used for social identity, apart from academic research and communication purposes. The article will be subjected to both qualitative and quantitative research methods. Therefore, unstructured and structured questionnaires, together with informal interviews will be used as data collecting techniques.